Systematic Literature Review: Inconsistencies and Developments in Ownership Structure and Board Characteristics in Sustainability Reporting - Mona Nur Adhillah; Inten Meutia; Shelly Febriana Kartasari (Journal of Social Research, 2025)
This study employs a Systematic Literature Review (SLR) method to analyze inconsistencies and developments in ownership structure and board characteristics concerning sustainability reporting. Sustainability reporting has emerged as a pivotal tool for corporations to showcase their economic, social, and environmental responsibilities. However, significant discrepancies exist in the relationship between ownership structures, board attributes, and the quality of sustainability disclosures globally. Drawing upon 37 relevant articles published between 2015 and 2024, this research identifies critical trends and gaps. Ownership structures, including foreign, institutional, and family ownership, show varied impacts on sustainability reporting across developed, developing, and mixed-economy countries. For instance, foreign ownership often drives transparency in developing nations due to external pressures, while governmental ownership exhibits mixed effects depending on regulatory and market dynamics. Similarly, board characteristics like gender diversity, independence, and the presence of sustainability committees significantly influence the quality of sustainability disclosures. These relationships, however, are subject to regional governance maturity and cultural norms. The study highlights the dominance of quantitative methodologies in existing literature, with limited exploration of mixed-method approaches. Findings also reveal that inconsistencies in results are rooted in differences in regulatory environments, market pressures, and cultural expectations. Developed nations exhibit greater adherence to stringent sustainability standards, while developing countries face challenges in harmonizing local priorities with global frameworks. By addressing these inconsistencies, this research contributes to advancing the understanding of ownership and governance dynamics in sustainability reporting. It also underscores the need for globally harmonized reporting standards to ensure consistent, high-quality sustainability practices.